Boomer - Miles, Ellen (Miles, Ellen. Puppy place., 2015)
"Lizzie's mom has three of her best friends coming over to visit for a long weekend when the Petersons get a call about Boomer, a big mixed breed puppy who needs a place to stay. Can Lizzie take care of him without ruining mom's plans?"--